2003
DOI: 10.1016/s0168-3659(02)00465-0
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic and hydrophobic cyclodextrins in a new sustained release oral formulation of nicardipine: in vitro evaluation and bioavailability studies in rabbits

Abstract: The feasibility of using complexes with cyclodextrins (CDs) in nicardipine (NC) controlled delivery has been examined, with a view to extending the pharmaceutical applications spectrum of these carriers. For a fast release fraction, a hydrophilic beta-cyclodextrin derivative (hydroxypropyl-beta-cyclodextrin) was employed to form a water-soluble complex. For the sustained-releasing portion, triacetyl-beta-cyclodextrin (TAbetaCD) was used to provide complexes with appropriate hydrophobicity. An optimal formulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…This hydrophobic drug has been administered intravenously, subcutaneously and transdermally [32,33]. Formation of inclusion complex with β-CD has been suggested to improve the solubility of NIC in aqueous solution [34,35]. Due to the poor solubility of NIC in aqueous phases and other routes of administration, it has been chosen as a model drug in this work.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This hydrophobic drug has been administered intravenously, subcutaneously and transdermally [32,33]. Formation of inclusion complex with β-CD has been suggested to improve the solubility of NIC in aqueous solution [34,35]. Due to the poor solubility of NIC in aqueous phases and other routes of administration, it has been chosen as a model drug in this work.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The compound was rapidly absorbed after oral administration with an absorption rate constant k a of approximately 3.6 h À1 . (AE )-DHP-014 demonstrated a relatively poor oral bioavailability (approximately 8%), which may due to poor solubility of the compound [7,8] and substantial first-pass extraction. It was reported that the two related 1,4-dihydropyridines, nicardipine and nitrendipine undergo extensive first-pass hepatic extraction after oral administration [9].…”
Section: Discussionmentioning
confidence: 99%
“…These derivatives are strong candidates for functional drug carriers to control the rate and/or time profi le of drug release. In fact, hydrophilic and hydrophobic CyDs modify the release rates of drugs [6,7,12].…”
Section: Fig 1 a Schematic Diagram Of 6-o-α-dmaltosyl-β-cyclodextrinmentioning
confidence: 99%
“…
small molecules and portions of large compounds, and it is now well known that CyDs possess multifunctional characteristics [6,7]. For instance, drugs encapsulated with CyDs provide more balanced biological activity in oral administration and serve the purpose of prolonged therapeutic effect [6].
…”
mentioning
confidence: 99%